2020
DOI: 10.1088/2057-1976/ab7bf9
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric 3D bioprinting for ophthalmological applications: process development and viability analysis of the technology

Abstract: Piezoelectric inkjet 3D bioprinting technology is a viable technique for ophthalmological applications. It provides versatility, high sensibility and accuracy, required in ophthalmological procedures. A process flow for biofabrication was described in detail and validated, using piezoelectric inkjet technology, for ophthalmological applications, in vitro and in situ, based on complex images. Ophthalmological problems were documented by diagnostic examinations and were fed to the flow as complex images. The Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These proposals were tested bioprinting with gel and water, as ink, and a script that uses a substrate photographic record with the predefined location to perform overprinting (Hoehne et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proposals were tested bioprinting with gel and water, as ink, and a script that uses a substrate photographic record with the predefined location to perform overprinting (Hoehne et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the research projects involve inkjet bioprinter, a kind of additive manufacturing (Tony et al 2023) in the treatment of some ophthalmic pathologies such as herpes and corneal ulcers (Hoehne et al 2020). This technology makes it possible to precisely build tissues that can be implanted to repair an injury or replace the function of an organ that is injured in order to mimic the tissue's natural characteristics.…”
Section: Background and Motivationmentioning
confidence: 99%
“…48 Piezoelectric inkjet bioprinting uses a piezoelectric actuator to produce droplets. 49 When an impulsive voltage is applied to a piezoelectric crystal, a rapid and reversible deformation occurs, causing a sudden change in the volume of the chamber, which leads to the transmission of acoustic waves that provide the necessary pressure pulse to surpass the surface tension at the injector inlet. 50 Kim et al demonstrated that polymer micro-patterning by inkjet printing controlled the cell adhesion geometry as shown in Fig.…”
Section: Inkjet Printersmentioning
confidence: 99%
“…Piezoelectric inkjet bioprinting, applies an actuator of piezoelectric nature in order to create droplets. In this case, the voltage provokes a rapid change in the chamber volume that results in the generation of acoustic waves, that provide a pulse of pressure for bioinking [39]. Electrostatic inkjet bioprinting is driven by the voltage given to a motor and a platen, provoking a bend on a platen that produces the bioink by extrusion.…”
Section: Droplet-based Bioprintingmentioning
confidence: 99%